Graphite Felt Decorated with Metal–Organic Framework-Derived Nanocomposite as Cathode for Vanadium Redox Flow Battery - Priya Lakshmanan; Chia-Hung Huang; Suba Devi Rengapillai; Yong-Song Chen; Wei-Ren Liu; Cheng-Liang Hsu; Sivakumar Marimuthu (Nanomaterials)
Fabricating electrodes with high electrocatalytic efficiency is crucial for the commercial feasibility of vanadium redox flow batteries (VRFBs). In this study, metal–organic framework-derived ZnO and Fe2O3 with a high specific surface area were successfully synthesized via high-energy ball milling. The nanocomposite material (ZnO-Fe2O3) was prepared through ultrasonication and coated on the graphite felt using dip coating, serving as the positive electrode for the VRFB. These modified electrodes control polarization losses, leading to high voltage efficiency (VE) and energy efficiency (EE), even at high current densities. Consequently, the nanocomposite-modified electrode shows VE of 87% and EE of 84% at 50 mA/cm2, surpassing the performance of individual materials. The nanocomposite material retains its EE without degradation over 250 cycles at a current density of 150 mA/cm2. This enhanced performance is due to improved kinetics and reduced losses in the VO2+/VO2+ redox couple, enabled by the nanocomposite material.